A COMPARATIVE ANALYSIS OF HYPERBARIC BUPIVACAINE AND LEVOBUPIVACAINE FOR SPINAL ANAESTHESIA IN CAESAREAN SECTIONS: A CLINICAL STUDY - Soubhagya Kumar Das; Nagendra Kumar Rajsamant; Chittaranjan Thatei; Satyajit Jena (Student's Journal of Health Research, 2023)
Introduction:  Spinal anesthesia for cesarean sections often involves the use of various local anesthetics. The research aimed to conduct a comparative study on the effects of intrathecal levobupivacaine and hyperbaric bupivacaine concerning sensory and motor blocks, hemodynamics, adverse effects, and recovery profiles. Methods:          A prospective observational study was conducted on 100 in-patients undergoing elective cesarean sections, excluding those with specific contraindications at SCB Medical College and Hospital in Cuttack, Odisha, India. Parameters including the (analgesic effect) sensory block and the (muscle paralysis) motor block, hemodynamic responses, and adverse effects, were observed and noted. Statistical analysis included descriptive statistics and parametric tests. Results:  Onset times for sensory and motor blocks were significantly different between the groups (p < 0.001). Levobupivacaine exhibited delayed onset compared to hyperbaric bupivacaine. Duration of sensory and motor blocks was significantly shorter with levobupivacaine (p < 0.001). Levobupivacaine demonstrated fewer incidences of bradycardia and hypotension compared to hyperbaric bupivacaine. Incidences of other adverse effects were similar between the groups. Conclusion:  The comparative analysis highlights the distinct characteristics of intrathecal levobupivacaine and hyperbaric bupivacaine in spinal anesthesia for lower-segment cesarean sections. Levobupivacaine demonstrated delayed onset of sensory block, potentially superior hemodynamic stability, and significantly lower occurrences of bradycardia. Recommendations:  Based on the observed outcomes, it is recommended that further comprehensive studies with larger sample sizes be conducted to validate the present findings. Extensive investigations are required to evaluate the long-term effects and rare adverse events associated with both agents. Additionally, multi-center trials could provide more robust evidence and enhance the generalizability of the results, aiding in the development of evidence-based guidelines for anesthetic choices in obstetric practice.